2013
DOI: 10.1371/journal.pone.0084440
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Service Use in Four European Countries: A Cross-National Retrospective Study via Representative Networks of General Practitioners

Abstract: BackgroundDue to a rising number of deaths from cancer and other chronic diseases a growing number of people experience complex symptoms and require palliative care towards the end of life. However, population-based data on the number of people receiving palliative care in Europe are scarce. The objective of this study is to examine, in four European countries, the number of people receiving palliative care in the last three months of life and the factors associated with receiving palliative care.MethodsCross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 36 publications
(48 reference statements)
1
77
0
Order By: Relevance
“…Research has shown that a large number of people with life-threatening illnesses prefer to and could be cared for in community-settings towards the end of life 4 28. Yet the results of our study show that all countries we studied face the challenge that large numbers of people are admitted to hospital towards the end of life.…”
Section: Discussionmentioning
confidence: 64%
“…Research has shown that a large number of people with life-threatening illnesses prefer to and could be cared for in community-settings towards the end of life 4 28. Yet the results of our study show that all countries we studied face the challenge that large numbers of people are admitted to hospital towards the end of life.…”
Section: Discussionmentioning
confidence: 64%
“…Family physicians are therefore considered to be instrumental in preventing inappropriate end-of-life hospital admissions. The family physician's gatekeeper role to hospital services is limited in Belgium, 33,34 however, because patients or families may autonomously decide to go to a hospital for specific problems without consulting any family physician. [34][35][36] The aim of this study was to explore the family physicians' perspectives of how they perceive their own role in preventing and guiding end-of-life hospital admissions and the difficulties they experience within such a role.…”
mentioning
confidence: 99%
“…The whole world is going through a demographic transition, with an increase in the number of elderly people and chronic noncommunicable diseases (CNCD) [1][2][3][4] such as cancer, diabetes and cardiovascular diseases, many of them in advanced stages. Because of the technological advances regarding the detection and treatment of these diseases, which once progressed rapidly and led to certain death, they now become chronic conditions, with an increasing number of symptoms and functional decline throughout the years.…”
Section: Introductionmentioning
confidence: 99%
“…The authors emphasized the importance of greater attention to patients with other conditions or diseases other than cancer, which end up dying without having access to PC. 2 This finding may be related to the fact that cancer has become a chronic disease, with decrease of mortality and improvements in prospects for treatment and cure. A study 14 pointed out that there is a noticeable drop in deaths from cancer in the South, Southeast and Center-West regions of Brazil, but this drop is only apparent in state capitals: the countryside population rates show a statistically significant increase.…”
mentioning
confidence: 99%
See 1 more Smart Citation